2012
DOI: 10.3382/ps.2011-01585
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of guanidinoacetic acid to broiler diets: Effects on performance, carcass characteristics, meat quality, and energy metabolism

Abstract: Creatine, (CREA) a central constituent in energy metabolism, is obtained from dietary animal protein or de novo synthesis from guanidinoacetic acid (GAA). Especially in all-vegetable diets, supplemental CREA or GAA may restore the CREA availability in tissues, and hence, improve performance. In this study, 768 one-d-old male Ross 308 broilers were assigned to 1 of 4 diets: negative control, all-vegetable corn-soybean-based; negative control supplemented with either 0.6 or 1.2 g of GAA per kilogram of feed; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
164
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(203 citation statements)
references
References 34 publications
22
164
3
1
Order By: Relevance
“…Also, supplemental GAA significantly improved FCR and breast meat yield, which might be related to increase muscle levels of creatine (Heger et al 2014). Creatine is necessary for energy haemostasis of cells, especially in birds fed the creatine-deficient diets exclusively based on vegetable ingredients such as corn and soybean meal (Michiels et al 2012). The GAA might be important in poultry nutrition in order to support overall energy homeostasis of the bird; an impact which is beyond the arginine sparing effect of GAA (Dilger et al 2013).…”
Section: Performance Parametersmentioning
confidence: 99%
“…Also, supplemental GAA significantly improved FCR and breast meat yield, which might be related to increase muscle levels of creatine (Heger et al 2014). Creatine is necessary for energy haemostasis of cells, especially in birds fed the creatine-deficient diets exclusively based on vegetable ingredients such as corn and soybean meal (Michiels et al 2012). The GAA might be important in poultry nutrition in order to support overall energy homeostasis of the bird; an impact which is beyond the arginine sparing effect of GAA (Dilger et al 2013).…”
Section: Performance Parametersmentioning
confidence: 99%
“…Recently, positive effects on growth performance were noticed when broilers were administered GAA. The transformation of GAA into creatine was evidenced by an increase in creatine levels (in serum and muscle) (Lemme et al, 2007a(Lemme et al, , 2007bRingel et al, 2008;Michiels et al, 2012;Carvalho et al, 2013). Moreover, GAA could be beneficial in broiler diets because it may be able to spare arginine, which is considered to be the fifth limiting amino acid in typical corn-soybean diets for broilers (Baker, 2009;Waguespack et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Creatine and phosphocreatine are not present in all cells, but only in high-energy expenditure cells, particularly in muscle cells. This system works as a ADP-ATP cycle backup in order to store and mobilize energy when necessary in the short term (Michiels et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Michiels et al (2012) reported that a diet supplemented with GAA (0.6 and 1.2 g/kg) markedly increased the creatine concentration in broiler breast meat. In this sense, GAA supplementation can be particularly important in diets for broiler strains with fast initial growth due to their high energy requirements to supply muscle creatine (Brosnan et al, 2009).…”
Section: Effects Of Guanidionoacetic Acid and Arginine Supplementatiomentioning
confidence: 99%